Implementation Of The Inquiry Learning Model On The Study Of AlQur'an Hadith Class X Man 01 Way Right Students (Case Study of Class X Students at MAN 1 Way Kanan) - Amin Siddik; Anggiani Sri Kinanti; Ahadi Sapron (Jurnal Iqra': Kajian Ilmu Pendidikan)
The implementation of education essentially has the main objective of producing students who are faithful, devoted to God Almighty, knowledgeable in science, technology and art. Apart from that, it is also able to produce graduate students who can keep up with current developments so that they are able to live independently in everyday life. The problem formulation for this thesis is: How to Implement the Inquiry Learning Model in the Al-Qur'an Hadith Subject (Case Study for Class X MAN 1 Way Kanan Students) for the 2020/2021 Academic Year. The focus of the problem in this research is: Want to know the implementation of the Inquiry learning model in the Al-Qur'an Hadith subject at MAN. 1. Right Way. The aim of this research is to determine the implementation of the inquiry learning model in Al-Qur'an Hadith lessons. Class X MAN 1 Way Kanan Students.The techniques/methods used to collect data in this research are observation, interviews, and documentation, and the type of approach the researcher uses is a case study approach. In analyzing the data that has been obtained, the researcher uses qualitative analysis,namely a research method used to research natural object conditions (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out in a triangulated (combined) manner, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization. The findings from research in the field are that there are still teachers who teach monotonously and verbally, there are still low learning achievements of students, and there are still students who do not understand how to read and write the Koran and its hadith. The conclusion of this research is that it is known that the Inquiry Learning Model is able to improve students' learning achievement in Al-Qur'an Hadith lessons. In other words, students' achievement in learning Al-Qur'an Hadith becomes better with the Inquiry learning process. This can be seen from the data from observations and documentation as well as the results of researcher interviews, the learning achievement in Al-Qur'an hadith subjects is high.